Inovasi Kegiatan dan Pembelajaran pada Masa Pandemi di Sekolah Alam Auliya Kendal - Nuriana Farhani (Universitas Negeri Jakarta, 2021)
This article aims to: 1) identify information about innovation activities and learning during the pandemic at the Auliya Kendal Nature School 2) analize whether the innovation of activities and learning at the Auliya Kendal Nature School during the pandemic can be implemented properly and effectively. The approach used this research is a descriptive qualitative approach. Data collection techniques used including interview, observation, and literature review. The results of this study indicate that the activities and learning at the Auliya Kendal Nature School include: 1) the innovation of activities and learning during the pandemic at the Auliya Kendal Nature School can be carried out well. Activities and learning are still cariied out in schools in accordance with health protocols to avoid the virus, 2) students continue to attend school with alternating schedules, and 3) learning is carried out by forming small groups. Each class with an average of 15-20 students is divided into two groups of 7-10 students. Each group is taught by one teacher at the same time with different learning class.